2022
DOI: 10.3390/ma15041453
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Affinity of Alkali-Activated Fly Ash Cubic Foams towards Heavy Metals Sorption

Abstract: In this work, alkali-activated fly ash-derived foams were produced at room temperature by direct foaming using aluminum powder. The 1 cm3 foams (cubes) were then evaluated as adsorbents to extract heavy metals from aqueous solutions. The foams’ selectivity towards lead, cadmium, zinc, and copper ions was evaluated in single, binary, and multicomponent ionic solutions. In the single ion assays, the foams showed much higher affinity towards lead, compared to the other heavy metals; at 10 ppm, the removal efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…It can be noticed that the FTIR pattern of MK had three broad features at approximately 1041 cm −1 , 784 cm −1 , and 439 cm −1 . The densest, asymmetrical, broad feature at 1041 cm −1 indicates the stretching of Si-O bonds in the amorphous MK structure [ 33 , 34 , 35 ]. The vibrations of the AlO 4 tetrahedra in MK were attributed to the broad band located at about 784 cm −1 [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be noticed that the FTIR pattern of MK had three broad features at approximately 1041 cm −1 , 784 cm −1 , and 439 cm −1 . The densest, asymmetrical, broad feature at 1041 cm −1 indicates the stretching of Si-O bonds in the amorphous MK structure [ 33 , 34 , 35 ]. The vibrations of the AlO 4 tetrahedra in MK were attributed to the broad band located at about 784 cm −1 [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was most likely caused by the water content of the RM [ 37 ]. The H-O-H stretching vibration in RM was related to the band at 1408 cm −1 [ 34 , 35 ]. For the RM spectrum, the characteristic band at 964 cm −1 corresponding to the asymmetric stretching vibrations of Si-O-Si and Si-O-Al was observed [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that the removal efficiency is affected by the heavy metals nature and follows the sequence in terms of affinity in a single component system: Pb 2+ > Cd 2+ > Zn 2+ > Cu 2+ . This tendency is related, among others, to the hydrated ionic radius and hydration enthalpy of the different heavy metals (Caetano et al, 2022).…”
Section: Heavy Metalsmentioning
confidence: 92%